PRINCIPLES OF THE DEVELOPMENT OF LOCAL BUDGETS IN THE CONDITIONS OF LOCAL GOVERNMENT REFORM - OGRAZANSKY, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to an overview of some of the main organizational and economic foundations of the development of local budgets in the conditions of local self-government reform. It was determined that local self-government is a manifestation of the democratic management of social development, which is based on the idea of citizen participation in solving community problems. The main functions of local self-government are the involvement of citizens in issues of local development, management of communal property, socio-economic and cultural development, provision of social services to the population. The powers of local self-government bodies include the preparation of community socio-economic development programs, the involvement of enterprises and ensuring the efficient use of resources. The implementation of the organizational and economic mechanism benefits all participants in the process, because the accumulation of taxes in the local budget contributes to the growth of the quality of life of the population, creates additional conditions for the development of enterprises, the creation of new jobs, and affects the formation of the investment climate. In the conditions of martial law, changes were made to a number of regulatory and legal documents regulating budgetary issues to ensure the smooth functioning of budgets at various levels during the war. The changes concerned the provision of prompt, continuous and timely implementation of local budgets, which provide for the needs of both residents and business entities of the OTG. To ensure the restoration of the work of enterprises and organizations in the liberated territories, local self-government bodies redistribute state aid. At the same time, the biggest changes in legislation related to the cancellation of mandatory taxes and deductions to the budgets of the OTG. Further scientific research in this direction concerns the improvement of the methodology for analyzing the development of local budgets in the context of local self-government reform. A number of regulatory and legal documents regulating budgetary issues under martial law were reviewed.